(untitled) (Palíndromo, 2020)
Discussing the urban landscape as a social construction, it was chosen for the work of Rochelle Costi “Tombo: Centro Novo, 2017” in which the artist presents the center of São Paulo that no longer exists, in images within archives. The body, the landscape and the trajectory of the city are intricated in a series of images that compel the public to leave their places of lovers. The installation was presented in an exhibition that discussed the city of São Paulo, based in Paulo Herkennhoff and Leno Veras as of Flusser’s proposition about this city. The article discusses Rochelle’s work relating art to sociology and anthropology, presenting the idea that contemporary objects, as well as the urban landscape, should be viewed in an interdisciplinary way.